2012
DOI: 10.1136/gutjnl-2012-303006
|View full text |Cite
|
Sign up to set email alerts
|

Plasma antibodies to oral bacteria and risk of pancreatic cancer in a large European prospective cohort study

Abstract: Objective Examine the relationship between antibodies to 25 oral bacteria and pancreatic cancer risk in a prospective cohort study. Design We measured antibodies to oral bacteria in prediagnosis blood samples from 405 pancreatic cancer cases and 416 matched controls, nested within the European Prospective Investigation into Cancer and Nutrition study (EPIC). Analyses were conducted using conditional logistic regression and additionally adjusted for smoking status and body mass index. Results Individuals wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
335
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(353 citation statements)
references
References 53 publications
11
335
3
4
Order By: Relevance
“…In a recent retrospective case-control study, oral bacteria measures in saliva were associated with pancreatic cancer [48]. Michaud et al [1] found increased levels of antibodies against specific commensal oral bacteria, which can inhibit growth of pathogenic bacteria and might reduce the risk of pancreatic cancer. The possible mechanisms include Toll-like receptor signaling, nitrosamine exposure and increase of systemic inflammation [49].…”
Section: Oral Microbiota and Pancreatic Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent retrospective case-control study, oral bacteria measures in saliva were associated with pancreatic cancer [48]. Michaud et al [1] found increased levels of antibodies against specific commensal oral bacteria, which can inhibit growth of pathogenic bacteria and might reduce the risk of pancreatic cancer. The possible mechanisms include Toll-like receptor signaling, nitrosamine exposure and increase of systemic inflammation [49].…”
Section: Oral Microbiota and Pancreatic Cancermentioning
confidence: 99%
“…Multiple observations have shown that oral microbiota overlap with the digestive tract microbiota, providing multiple avenues for dissemination in dysbiosis [1]. In a recent retrospective case-control study, oral bacteria measures in saliva were associated with pancreatic cancer [48].…”
Section: Oral Microbiota and Pancreatic Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…This result may support the idea that periodontal diseases increase the risk of pancreatic cancer. 15 Their study also reported that higher serum levels of P. gingivalis (ATCC 53978) may be the best marker for the higher burden of the bacteria and invasive periodontal diseases which may justify why this bacterium is the only periodontal pathogen possibly correlated with higher risk of pancreatic cancer. Also, a recent study compared the saliva samples of healthy individuals and those with pancreatic cancer patients and reported that there was a significant relationship between higher prevalence of P. gingivalis and this type of cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, in an independent validation using new saliva samples from 28 pancreatic cancer patients and 28 healthy controls, only Neisseria elongata and Streptococcus mitis were useful in distinguishing patients with pancreatic cancer from healthy subjects, with an area under the curve value of 0.90 (95% CI: 0.78-0.96, p < 0.0001), a 96.4% sensitivity and a 82.1% specificity (Farrell et al 2012). Moreover, using an immunoblot array, Michaud et al (2013) evaluated antibodies detected against 25 oral bacteria in the serum of 405 pancreatic cancer patients and 416 healthy controls. They observed that 6% of the patients with high antibody titres against Porphyromonas gingivalis (>200 ng/mL) had an adjusted odds ratio (OR) of 2.14 (95% CI: 1.05-4.36) for pancreatic cancer as compared with those with undetectable or lower levels.…”
Section: Gastric Carcinomamentioning
confidence: 99%